2017
DOI: 10.21676/2389783x.1737
|View full text |Cite
|
Sign up to set email alerts
|

Utilidad de menopause rating scale (mrs) en indígenas colombianas en climaterio

Abstract: 8Recibido en agosto 24 de 2015 Aceptado en febrero 05 de 2016 RESUMENLa Menopause Rating Scale (MRS) se compone teóricamente de tres dimensiones que evalúan síntomas somáticos, emocionales y urogenitales relacionados con la menopausia. La utilidad de las escalas varía según las características poblacionales y no se cuenta con investigaciones que corroboren estas dimensiones en población indígena. El objetivo fue evaluar la utilidad de las dimensiones y confiabilidad de MRS en indígenas colombianas. Se realizó … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
2
1
1
Order By: Relevance
“…It should be noted, however, that differences can be found in the global MRS scores, which would impact the symptomatological levels presented. In the present study, the global MRS score found was higher than that of other studies (16,21) ; this difference can be explained by cultural, economic and social differences, influencing the signs and symptoms of women and modifying the score of the domains (22) .…”
Section: Sleep Quality and Its Association With Menopausal And Climacteric Symptomscontrasting
confidence: 87%
“…It should be noted, however, that differences can be found in the global MRS scores, which would impact the symptomatological levels presented. In the present study, the global MRS score found was higher than that of other studies (16,21) ; this difference can be explained by cultural, economic and social differences, influencing the signs and symptoms of women and modifying the score of the domains (22) .…”
Section: Sleep Quality and Its Association With Menopausal And Climacteric Symptomscontrasting
confidence: 87%
“…Las últimas cuatro opciones de respuesta, se consideran presencia del síntoma (4). En una población menopaúsica colombiana se señaló alfa de Cronbach de 0,86 (9). Al final de cada semana se revisaban los formularios diligenciados.…”
Section: Tamaño De La Muestraunclassified
“…It has been translated and validated in several languages, including Spanish. 20,28 In a group of Colombian women, Monterrosa et al 28,29 found a reliability of 0.86 through Cronbach's α. In determining internal consistency for the included women in this study, a Cronbach's α was found to be 0.80 for the Menopause Rating Scale.…”
Section: Menopause Rating Scale (Mrs)mentioning
confidence: 99%